2014
DOI: 10.1111/1574-6968.12402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the cell life-cycle on bacteriophage T4 infection

Abstract: Synchronized Escherichia coli cultures were infected with bacteriophage T4 at discrete points in the cell growth cycle. The cell cycle had a significant impact on the outcome of infection. Cell burst size was smallest for newly formed cells and increased dramatically as these progressed in the cell cycle. The largest burst sizes were achieved when infecting cells immediately prior to cell division. When cells were infected during cell division, the burst size was reduced back to its initial value. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Another theory on the timing of infection by cyanomyoviruses is that late infection coincides with the S/G2 phases in the host cell cycle, in which the host genome was already replicated but the cell hasn't divided yet, the logic being that there would be double the amount of nucleotides available for synthesis of phage genomes 63 . This is indeed the case in the T4 phage of Escherichia coli 64 . Evidence from cultures 65,66 and from environmental samples 67 indicate that for at least some strains of Prochlorococcus the host cells divide at dawn, which would imply that the bulk of phage transcription occurs during the night, and may also explain why we were unable to assemble cyanomyovirus genomes from our metatranscriptomes.…”
Section: Discussionmentioning
confidence: 60%
“…Another theory on the timing of infection by cyanomyoviruses is that late infection coincides with the S/G2 phases in the host cell cycle, in which the host genome was already replicated but the cell hasn't divided yet, the logic being that there would be double the amount of nucleotides available for synthesis of phage genomes 63 . This is indeed the case in the T4 phage of Escherichia coli 64 . Evidence from cultures 65,66 and from environmental samples 67 indicate that for at least some strains of Prochlorococcus the host cells divide at dawn, which would imply that the bulk of phage transcription occurs during the night, and may also explain why we were unable to assemble cyanomyovirus genomes from our metatranscriptomes.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, the lack of model systems to study inefficient infections (e.g., those with lower fraction of infected/lysed cells and long latent periods) is problematic, as natural ecosystems are dynamic and environmental conditions impact host diversity, density and/or physiology, as well as the efficiency of phage–host interactions (You et al , 2002; Abedon et al , 2003; Shao and Wang, 2008; Stocker, 2012; Mojica and Brussaard, 2014; Storms et al , 2014; Zeglin, 2015). To date, work on infection efficiencies is mostly theoretical (Abedon et al , 2001; You et al , 2002; Bragg and Chisholm, 2008) and there is a need for new phage—host model systems, particularly those displaying inefficient infections and that are relevant in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on phages infecting Escherichia coli showed that the largest burst size was achieved after the completion of host DNA replication and immediately prior to cell division (Starka, 1962;Storms et al, 2014). This is likely due to the increased availability of intracellular resources for the formation of phage progeny (Storms et al, 2014).…”
Section: Cyanophage Infection and The Host's Cell Cyclementioning
confidence: 99%
“…This is likely due to the increased availability of intracellular resources for the formation of phage progeny (Storms et al, 2014). Under light-dark cycles, S. elongatus PCC 7942 cells divide mainly during the daytime and stop dividing early at night (Mori et al, 1996).…”
Section: Cyanophage Infection and The Host's Cell Cyclementioning
confidence: 99%